Dataset for Geomorphology and climate interact to control organic carbon stock and age in mountain river valley bottoms - Scott, Daniel; Wohl, Ellen (Colorado State University. Libraries, 2018)
Organic carbon (OC) stored in dead vegetation and soil represents a massive and relatively sensitive pool of carbon whose distribution and residence time affects global climate. Mountain river basins can store large OC stocks. However, the distribution, magnitude, and residence time of OC stored in mountain river valley bottoms remain unquantified on broad scales, hampering understanding of how these regions contribute to terrestrial OC cycling. We compare four disparate mountain river basins to show that mountain river valley bottoms store substantial OC stocks in floodplain soil and downed wood that vary with valley bottom form and geomorphic processes. We quantify soil OC radiocarbon age to show that soil burial is essential to preserving old OC. Valley bottom morphology, soil retention, and vegetation dynamics determine partitioning of valley bottom OC between soil and wood, implying that modern biogeomorphic process and the legacy of past erosion regulate the modern distribution of OC in river networks. The age of the floodplain soil OC pool and the distribution of OC between wood and soil imply that mountain rivers are highly sensitive to alterations in soil and wood retention, which may have both short- and long-term feedbacks with the distribution of OC between the land and atmosphere.
These data describe organic carbon stocks and ages in rivers and associated characteristics. These data were collected during 2016 and 2017, and support analyses described in the journal article listed below.
Department of Geosciences